Correlation between Hasford Score with Early Molecular Response in Patients with Chronic Myeloid Leukemia in Chronic Phase Treated with Imatinib - I Dewa Made Widi Hersana (Oriental Scientific Publishing Company, 2019)
The aim of the study is to to determine correlation Hasford score and early molecular response in chronic phase BCR-ABL-Positive CML patients treated with imatinib. This is an longitudinal observational study in newly diagnosed patients of CML chronic phase BCR-ABL-Positive treated imatinib from Januari 2017 to September 2017. Patients were stratified according to Hasford score at diagnosis. Q-PCR(Quantitative RT-PCR) were used to monitor BCR-ABL transcription levels after 3 months of imatinib treatment. Correlation between Hasford score with early molecular response were analyzed using Koefisien Kontingensi’s correlation test. Results: Thirty five patients were enrolled in this study consist of 13 male and 22 female. After 3 months of imatinib treatment, EMR were 5 patients (83.3%), 11 patients (61.1%) and 2 patients (18.2%) in low, intermediate, and high risk group patients, respectively. Koefisien kontigensi test showed that there was significant correlation between Hasford score and EMR (p=0.018; r=0.431). The Hasford score correlated to early molecular response in chronic phase BCR-ABL-positive CML patients received imatinib.